Improvement in fluid loss control and viscosity of water-based drilling mud under high temperature and sodium chloride salt conditions using nanohydroxyapatite - Oseh, Jeffrey O.; M.N.A.M., Norddin; Duru, Ugochukwu I.; Ngouangna, Eugene Ngwana; Issham, Ismail; Gbadamosi, Afeez Olayinka; Agi, Augustine Aja; Yahya, Muftahu N.; Oguamah, Ifeanyi A. (Sultan Qaboos University, 2024)
It is difficult to drill efficiently with bentonite (BN)-based mud (BN-WBM) or water-based muds (WBMs) in high-salt electrolytes and deep wells. This is because the fluid's rheological parameters and filtration properties change in undesirable ways, affecting the well's production efficiency. To fix this, a high-salt and high-temperature-resistant nanohydroxyapatite (nanoHAp) additive was designed using sodium dodecyl sulphate (SDS). 0.1 to 0.5 wt% nanoHAp was added to WBMs, and a salt-resistant BN-WBM with nanoHAp was formulated with 4.8 wt% BN, 5.0 wt% sodium chloride (NaCl), and 0.5 wt% nanoHAp. At 25, 150, 180, and 210° C, the filtration and rheological characteristics of the drilling muds were evaluated. The findings revealed that between 25 and 210° C, nanoHAp increased the viscosity of the WBM by 15–139% at a 1021 s-1 shear rate. It also controlled the fluid loss of the WBM from 12.1-44.6 mL to 6.7-21.8 mL at all temperatures. It serves as an anti-salt agent by decreasing the NaCl-contaminated BN's viscosity by 57% compared to the reference value of 20.8 mPa. s at a shear rate of 1021 s-1. Further, it reduced the fluid loss by 56.8%, from 169 mL to 73 mL at 210° C. The nanoHAp surface has anionic sulphate head groups of SDS that efficiently attach to the BN surface. This keeps the Na+ ions from attacking the plate-like structure of the BN. This study reveals that nanoHAp has the capacity to inhibit BN coalescence and flocculation under saturated Na+ solutions and at high temperatures.